Effects of copper exposure on hatching success and early larval survival in marbled salamanders, Ambystoma opacum. (21st May 2014) - Soteropoulos, Diana L.; Lance, Stacey L.; Flynn, R. Wesley; Scott, David E.
Abstract The creation of wetlands, such as urban and industrial ponds, has increased in recent decades, and these wetlands often become enriched in pollutants over time. One metal contaminant trapped in created wetlands is copper (Cu2+). Copper concentrations in sediments and overlying water may affect amphibian species that breed in created wetlands. The authors analyzed the Cu concentration in dried sediments from a contaminated wetland and the levels of aqueous Cu released after flooding the sediments with different volumes of water, mimicking low, medium, and high pond‐filling events. Eggs and larvae of Ambystoma opacum Gravenhorst, a salamander that lays eggs on the sediments in dry pond beds that hatch on pond‐filling, were exposed to a range of Cu concentrations that bracketed potential aqueous Cu levels in created wetlands. Embryo survival varied among clutches, but increased Cu levels did not affect embryo survival. At Cu concentrations of 500 µg/L or greater, however, embryos hatched earlier, and the aquatic larvae died shortly after hatching. Because Cu concentrations in sediments increase over time in created wetlands, even relatively tolerant species such as A. opacum may be affected by Cu levels in the posthatching environment. Environ Toxicol Chem 2014;33:1631–1637. © 2014 SETAC